T'ai chi the essential introductory guide - Peck, Alan (Vermilion, 1996)
T'ai Chi is recognized for its slow, graceful movements. This introduction teaches a flexible and yielding response to confrontation and the physical, mental and spiritual benefits practising T'ai Chi can bring. It also includes information on finding a class, basic exercises and techniques.